Recommended Carrot Production and Handling Practices - Listowell Aditwin Akologo; Harrison Kwame Dapaah; Julius Yirzagla (Emerging Issues in Agricultural Sciences Vol. 6, 2023)
The aim of this book chapter is to highlight salient carrot production and handling practices to provide some relevant information to farmers, agricultural-service providers and other actors along the carrot value chain. The chapter is an output of research that examined the contribution and improvement of cowpea-based Biological Nitrogen Fixation (BNF) in carrot production in the Ashanti Mampong Municipality in the Ashanti Region of Ghana to propel carrot production to sustainable levels. Carrot production is a widespread economic activity within the Municipality which supplies vegetables especially carrot to other urban centres such as Kumasi within the Ashanti Region of Ghana. Carrot is a valued exotic vegetable in Ghana, mostly used in combination with other vegetables in preparing soups, stews, salads and drinks. Demand for carrots therefore, remains high especially in urban centres. A major constraint to carrot production is poor soil fertility. Carrot farmers generally experience high production costs as a result of inorganic fertilizer application. The use of legumes such as cowpea for nitrogen fixation leading to soil fertility enhancement provides a viable alternative for sustainable crop production. It is envisaged that this book chapter will serve as a valuable reference material for actors along the carrot value chain in Ghana and other parts of the world.